Projection of Biodiesel Production in Indonesia to Achieve National Mandatory Blending in 2025 using System Dynamics Modeling - Mayasari, Fitriyanti; Dalimi, Rinaldy; Purwanto, Widodo Wahyu (International Journal of Energy Economics and Policy, 2019)
Biodiesel has been produced since 2006 in Indonesia and regulation of biodiesel blending has been set, but the actual blending rate was never reached the target. The research aims to increase biodiesel production to achieve mandatory target and reduce diesel oil import. It will project biodiesel production achieving demand in Indonesia until 2025 and proposes some strategies to increase blended biodiesel production by constructing system dynamics modeling. The research shows, there are 3 scenarios to increase biodiesel production; palm oil cultivation land, palm oil productivity and refined CPO shared. To meet blended biodiesel demand, cultivation land should be increased to 3.2-6.5% per year, productivity should be fixed to 12.54 ton/ha and refined CPO shared should be adjusted to 56.9-65.4%. This scenario also will reduce diesel oil import to 7.16–9.82 million kL per year. Refined CPO shared is the most influenced variable; therefore the government should consider to make refined CPO export limitation policy. Keywords: Blended Biodiesel Production; System Dynamics Modeling; Refined CPO Export JEL Classification: Z DOI: https://doi.org/10.32479/ijeep.8319